2015
DOI: 10.4103/0973-1482.168183
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of concurrent chemoradiotherapy in the treatment of locoregionally advanced nasopharyngeal carcinoma

Abstract: The results suggested that CCRT was more beneficial when compared with RT alone in locoregionally advanced NPC patients. Further study is needed to perform to confirm this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although NPC is radiation sensitive, the outcomes of patients with advanced stages of the disease are not satisfactory, owing to local recurrence and chemoresistance. 2 , 3 The outcomes remain poor in a substantial number of NPC patients, with relapse and distant metastasis often being reported. 4 , 5 Hence, it is imperative to study the molecular mechanisms underlying the progression of NPC to improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although NPC is radiation sensitive, the outcomes of patients with advanced stages of the disease are not satisfactory, owing to local recurrence and chemoresistance. 2 , 3 The outcomes remain poor in a substantial number of NPC patients, with relapse and distant metastasis often being reported. 4 , 5 Hence, it is imperative to study the molecular mechanisms underlying the progression of NPC to improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…10,42 Numerous studies reported the superiority of CCRT for tumor control and survival in patients with LA-NPC. 6,7,22,23,[43][44][45] The landmark MAC-NPC meta-analysis confirmed that the addition of chemotherapy to RT significantly improved OS in nonmetastatic stage II-IV NPC (HR 0.79; P < .001). 7 IC has received OS benefit when added to CCRT in several trials.…”
Section: Discussionmentioning
confidence: 92%
“…However, owing to the high rate of recurrence, and resistance to chemotherapy, patients with advanced stages usually have a poor prognosis. 3 , 4 Therefore, the development of novel therapeutic targets, to improve the survival and quality of life of these patients is crucial.…”
Section: Introductionmentioning
confidence: 99%